SCIENTIFIC PERIODICALS IN THE UNIVERSITY OF MALAYA LIBRARY-A BIBLIOMETRIC EVALUATION - Sen, Bimal Kanti; Awang Ngah, Zainab; Sen, B.K.; Awang Ngah, Zainab (Malaysian Journal of Library and Information Science, 2017)
Sen, B. K., & Zainab, A. N. (1996). Scientific periodicals in the University of Malaya Library-a bibliometric evaluation. Malaysian Journal of Library & Information Science, Vol.1, no. 2: 63-77 Examines the availability of top ranking scientific periodicals in the University of Malaya Library (UML). The study is based on journal titles listed in the Subject Category Listing of the Journal Citation Report (JCR), 1994 which covers 16 subject fields such as Biochemistry and Molecular Biology; Biology; Cell Biology; Chemistry; Analytical Chemistry; Physical Chemistry, Ecology; Genetics and Hereditary, Geology; Geosciences; Mathematics; Applied Mathematics; Physics; Applied Physics; Plant Sciences and Zoology. The study shows that of the first fifty titles listed under each category 72% are available in Plant Sciences and Mathematics, 60-70% are available in Geosciences, Geology, Ecology and Biochemistry and Molecular Biology, 50-59% are available in Zoology, Applied physics, Physics, Applied Mathematics, Genetics and Heredity, Physical Chemistry and Chemistry. The availability in other science fields such as Analytic Chemistry, Cell Biology and Biology is 46%.